Bacteriological and Molecular Characterization of Extended Spectrum Β-Lactamases in Clinical Isolates of Klebsiella Pneumoniae Isolated From Kurdistan Region, Iraq. - KHALID, HAVAL MOHAMMED; YOUSIF, SAMIRA YOUNIS; JUBRAEL, JALADET M. S. (Science Journal of University of Zakho, 2013)
A total of 275 clinical isolates of Klebsiella pneumoniae were collected from three general hospitals in Duhok, Erbil, and Sulymania, during the period September 2010 to June 2011. The Minimum Inhibitory Concentration (MIC) of these isolates was measured using the Gram-negative susceptibility card (GNC) of Phoenix system. Only 187 ESBL producing K. pneumoniae isolates were detected by this system. These isolates were confirmed as 100% ESBLs producers by the Double Disk Synergy Test (DDST). All 187 K. pneumoniae isolates were 100% resistant to ampicillin, cefazolin, cefepime, ceftriaxone, cefotaxime, cefuroxime, ceftazidime, and aztreonam. These isolates showed different percentages of resistance 81.8%, 68.5%, 65.8%, 52.4%, 50.3%, 34.2%, 25.2%, and 12.3% towards, ampicillin/sulbactam, gentamicin, trimethoprime-sulfamethoxazole, ciprofloxacin, piperacillin-tazobactam, amikacin, amoxicillin-clavulanate, and levofloxacin respectively. Molecular characterization by PCR was employed using specific primers for three different ESBLs (TEM, SHV, and CTX-M). Results obtained revealed that SHV-type ESBLs were the most common ESBL occurring in 87% of the isolates with phenotypic evidence of ESBLs production. While those for TEM-type and CTX-M-type were 60% and 58% respectively.